Evaluation of the Cause of Pertalite Tank Fire at PT X with the Swiss Cheese Method - Yoganza Arrunata, Daffa; Qodri Z, Ainul; Nadya Oktavia, Siti; Alisia, Salma; Thariq Ramadhan, Ilham; Sulistiyo Nugroho, Budi (Sahabat Publikasi, 2024)
Work accidents are a risk that can occur in various industrial sectors, including the oil and gas sector which has a high potential for danger. This article discusses the case of a pertalite tank fire at PT X, which became one of the significant incidents in the oil refinery industry in Indonesia. This study aims to analyze the causes of the incident, the impact caused, and preventive efforts that can be made to minimize similar risks in the future. Data was obtained through document reviews, incident investigation reports, and literature related to industrial fires. The results of the analysis showed that this fire was caused by a combination of technical factors, such as the failure of the tank safety system, and human factors, including a lack of compliance with safety procedures. The impacts caused include significant material losses, operational disruptions, and environmental impacts and the health of the surrounding community. To prevent similar incidents, the recommendations included increased periodic inspections, improvement of standard operating procedures (SOPs), occupational safety training for employees, and the application of more advanced fire detection technology. This study is expected to be an evaluation material for similar industries to improve risk management and occupational safety systems